2016
DOI: 10.29057/icbi.v3i6.573
|View full text |Cite
|
Sign up to set email alerts
|

Evaluación de las propiedades fisicoquímicas de almidones de diferentes cereales

Abstract: En el presente proyecto de investigación se estudiaron las características fisicoquímicas y morfológicas de polisacáridos de avena, arroz, cebada, mijo y maíz. La composición química se determinó mediante un análisis proximal, donde se encontró que el almidón de arroz contenía 0.49% de cenizas, 2.71% de proteína y 96.79% de carbohidratos. El almidón de cebada presentó 0.76% de cenizas, 2.85% de proteína y 96.38% de carbohidratos. En el almidón de mijo se encontró 0.92% de cenizas, 2.98% de proteínas y 96.09% d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
1
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
0
1
1
Order By: Relevance
“…Mello et al [6] explained that said reduction was due to the washing of starch during and after acetylation that caused a loss of minerals. On the other hand, Cantellano et al [7] reported 2.71% protein in rice starch resulting higher than those found in this work where a value of 0.60% in NS and 0.45% in MS was obtained. The protein content in the starch could be affected during the isolation method.…”
Section: Introductioncontrasting
confidence: 86%
“…Mello et al [6] explained that said reduction was due to the washing of starch during and after acetylation that caused a loss of minerals. On the other hand, Cantellano et al [7] reported 2.71% protein in rice starch resulting higher than those found in this work where a value of 0.60% in NS and 0.45% in MS was obtained. The protein content in the starch could be affected during the isolation method.…”
Section: Introductioncontrasting
confidence: 86%
“…TRADING COMPANY; los emulsionantes fueron ésteres de monoglicéridos y del ácido diacetil tartárico (DATEM) y estearoil 2-lactilato de sodio (SSL) (CIMPA s.a.s. ); finalmente se adicionó almidón de maíz (PROMIDEX) debido a que presenta las características más similares al almidón de trigo (Castellano-Jaramillo et. al, 2016).…”
Section: Selección De Los Aditivosunclassified